2021
DOI: 10.1111/head.14151
|View full text |Cite
|
Sign up to set email alerts
|

Learning the full impact of migraine through patient voices: A qualitative study

Abstract: Objective: To better characterize the ways that migraine affects multiple domains of life.Background: Further understanding of migraine burden is needed. Methods: Adults with migraine randomized to mindfulness-based stress reduction or headache education arms (n = 81) in two separate randomized clinical trials participated in semistructured in-person qualitative interviews conducted after the interventions. Interviews queried participants on migraine impact on life and were audio-recorded, transcribed, and sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 51 publications
0
50
0
4
Order By: Relevance
“…“If you didn't have migraine, how would your life be different?” and “What are your expectations for this visit?” [ 1 ]. These questions help neurologists understand the many ways migraine impacts their patients' lives and help target the visit on what matters to the patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…“If you didn't have migraine, how would your life be different?” and “What are your expectations for this visit?” [ 1 ]. These questions help neurologists understand the many ways migraine impacts their patients' lives and help target the visit on what matters to the patients.…”
Section: Introductionmentioning
confidence: 99%
“…These questions help neurologists understand the many ways migraine impacts their patients' lives and help target the visit on what matters to the patients. Despite acute and/or preventive treatment, migraine negatively impacts the lives of 90% of people with migraine in many domains including work, cognitive function, and emotional health [ 1 ]. Migraine is the leading cause of disability in adults under age 50 years and the second leading cause of disability at all other ages in the world [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are presented in the current issue of Headache in our publication "Learning the full impact of migraine through patient voices: A qualitative study." 4 The findings from our large qualitative study, with 81 participants who provided nearly 3300 min of recorded interviews across two clinical trials conducted in two cities, highlight how people with migraine experience the disease as a major burden despite widespread treatment availability. Most participants in our study were using acute and/ or preventive medications, yet 90% reported that migraine still had a negative overall impact on their lives.…”
Section: G U E S T E D I T O R I a Lmentioning
confidence: 92%
“…5,6 Having their experiences heard and validated builds rapport, the foundation of a productive therapeutic relationship. The very process of "telling your story" can itself be therapeutic for patients, 4 as narrative medicine has significant value. 7,8 Understanding the ways in which migraine most impacts a patient's life can help providers and patients develop shared agreement on the goals of migraine therapy, help the provider select a therapeutic option targeted to the patient's goals, and improve patient adherence to a collaboratively developed treatment plan.…”
Section: G U E S T E D I T O R I a Lmentioning
confidence: 99%